THE USE OF PHRASES WITH THE COMPONENT OF COLOR NAMES AS A MANIFESTATION OF THE NATIONAL IDENTITY OF UKRAINIANS - Загоруйко, Н. (Modern engineering and innovative technologies, 2024)
The article examines the universal and ethnic features of color names as а part of phraseological units - linguistic and cultural signs of national specificity. High frequency of use of color names in anthropocentric phraseology. It has been proven that t